Understanding Consumer Perspectives of Bio-Based Products—A Comparative Case Study from Ireland and The Netherlands - Gaffey, James; McMahon, Helena; Marsh, Emily; Vehmas, Kaisa; Kymäläinen, Tiina; Vos, John (Sustainability, 2021)
The bioeconomy can support Europe’s transition to a low-carbon economy and help to meet key international, European and member state sustainability targets through the provision of bio-based products and energy derived from sustainably sourced biomass. A successful implementation of a bio-based economy in Europe will, however, require a profound transformation of our production and consumption patterns. Consumer behavior will play a major role in supporting the successful transition to a bio-based economy. This paper uses a structured quantitative survey approach to gain an understanding of consumer perspectives in relation to bio-based products. Conducted among 18–75-year-old consumers in Ireland and the Netherlands, the study indicates that consumers in both countries have a relatively positive outlook regarding bio-based products, with Irish consumers showing a slightly more positive outlook. The study finds that a larger majority of Irish consumers would prefer buying bio-based products as opposed to fossil-based products, while Irish consumers also have a slightly more positive impression than Dutch consumers that their consumer choices can be beneficial for the environment.